DENTAL AND ORAL HEALTH CARE FOR CLIENT TN. MS (22 YEARS) WITH ANXIETY/FEAR OF TOOTH EXTRACTION (Politeknik Kesehatan Kemenkes Bandung, 2020)
Anxiety is an individual or group situation that experiences feelings of anxiety (judgment and opinion) and autonomic system activities in response to vague and nonspecific threats. An ideal tooth extraction is the pain-free extraction of a single tooth, or tooth root, with minimal trauma to the supporting tissues of the tooth, so that the extractions can heal completely. The purpose of the preparation of this report is to identify the management of dental and oral health care for client Mr. MS (22 years) with anxiety / fear of tooth extraction. This type of research is a case report with the concept of dental and oral health care consisting of the process of assessment, diagnosis, planning, implementation, and evaluation. This report also explains about dental anxiety and tooth extraction. To the client MS found 1 tooth had to be extracted because of caries that was not treated / patched. The implementation provided is referring the client to extract the remaining root. The evaluation results show that there are 1 human needs that have not been met and 2 other basic human needs only partially met. Key words : Care for Oral and Dental Health, Caries, Tooth Extraction, Basic Human Needs.